UTILIZAÇÃO DE RECURSOS ERGOGÊNICOS NUTRICIONAIS E/OU FARMACOLÓGICOS EM UMA ACADEMIA DA CIDADE DE BARRA DO PIRAÍ, RJ - Luana Palmeira Pereira (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
The habit of doing workouts combined with use of nutritional ergogenic or pharmacological has grown considerably in the last years. Whether for esthetic reasons or in order to improve some performance aspects, athletes consume a large amount of these products. In this sense, the purpose of this study is: survey the consumers profile of a nutritional ergogenic resources in Barra do Piraí gyms (RJ state), enumerate the products used by users of both sexes and verify the prescription source of these products to researched participants, ascertain if the participants achieved the expected results with use of these products and if they caused any side effects. This is an observational study, which evaluated 101 athletes of both genders and social classes. It was found that the majority of participants 75% (n = 76) reported the use of nutritional ergogenic or pharmacological, with the highest prevalence among men. Two products were the most consumed: whey protein 56.57% (n = 34) and creatine 42.10% (n = 25). The majority 45% (n = 34) reported consuming ergogenic without an expert guidance. Therefore, that the study shows the importance of each time more the professional in the field of nutrition be inserted in the sports ground for possible explanations about the effects of this product type is found between sportsman.